Decorin levels and cardiometabolic function after endurance exercise - de Fontes-Junior, Antônio Alves; de Sousa, Cesar Augustus Zocoler; de Oliveira, Leandro Barbosa; Sierra, Ana Paula Renno; Cury-Boaventura, Maria Fernanda (Frontiers in Physiology, 2025)
IntroductionDecorin is secreted from myotubes in response to exercise and plays a vital role in repairing and regenerate skeletal and cardiac muscle. The role of decorin levels in cardiometabolic function after endurance exercise was investigated.MethodsFifty-six male amateur runners, aged 30 to 55 years, participated in this study. Plasma decorin levels were determined and cardiopulmonary exercise test (CPET) was performed using a breath-by-breath system before and after the marathon.ResultsCorrelations between decorin levels and CPET parameters were assessed using Spearman’s rank correlation test. Runners were categorized into percentiles based on decorin concentrations, and group differences were analyzed using the Kruskal-Wallis test followed by Dunn’s post hoc multiple comparisons.We observed impairments in peak VO2 and in the Oxygen Uptake Efficiency Slope (OUES) following the race. Plasma decorin levels increased approximately two-fold immediately after the race. Post-race decorin concentrations were positively correlated with maximum speed (km/h), VO2 (mL/kg/min), VE/VCO2, VE/VCO2 slope, OUES, and the rate of change in VE/VCO2 and VE/VCO2 slope. Runners with plasma decorin levels below the 25th percentile exhibited significantly lower OUES, while those above the 75th percentile demonstrated higher maximum speed, VE/VCO2, rate of change in VE/VCO2 slope, and VCO2 compared to individuals in the lowest quartile.DiscussionOverall, decorin levels were associated with several CPET parameters, suggesting that runners with varying decorin concentrations may exhibit distinct respiratory and/or metabolic profiles. The potential influence of an elevated VE/VCO2 slope on cardiometabolic responses in runners with higher decorin levels warrants further investigation.